2019
DOI: 10.1111/gcb.14851
|View full text |Cite
|
Sign up to set email alerts
|

Carbon for nutrient exchange between arbuscular mycorrhizal fungi and wheat varies according to cultivar and changes in atmospheric carbon dioxide concentration

Abstract: Arbuscular mycorrhizal fungi (AMF) form symbioses with most crops, potentially improving their nutrient assimilation and growth. The effects of cultivar and atmospheric CO2 concentration ([CO2]) on wheat–AMF carbon‐for‐nutrient exchange remain critical knowledge gaps in the exploitation of AMF for future sustainable agricultural practices within the context of global climate change. We used stable and radioisotope tracers (15N, 33P, 14C) to quantify AMF‐mediated nutrient uptake and fungal acquisition of plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 109 publications
(228 reference statements)
5
52
0
2
Order By: Relevance
“…Comparing the effects of organic and conventional AM fungal field inoculum on crop growth and yield can importantly inform efforts to increase the effectiveness of sustainable agriculture. It has been known that cultivars of wheat exhibit different responses to mycorrhizal fungal inoculation [11,12,19,20]. Although earlier studies found that older cultivars strongly responded to AM fungal inoculation, later studies provide mixed results [16,18,21].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the effects of organic and conventional AM fungal field inoculum on crop growth and yield can importantly inform efforts to increase the effectiveness of sustainable agriculture. It has been known that cultivars of wheat exhibit different responses to mycorrhizal fungal inoculation [11,12,19,20]. Although earlier studies found that older cultivars strongly responded to AM fungal inoculation, later studies provide mixed results [16,18,21].…”
Section: Plos Onementioning
confidence: 99%
“…Wheat cultivars associate with different AM fungal communities in their roots [17] and may respond differently to AM fungal inoculation in terms of growth, root colonization and carbon for nutrient exchange [18][19][20]. Hetrick et al [10] suggested that the age of a cultivar (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Assimilation of N and P via AMF was quantified using 33 P and 15 N tracers when plants were 11 weeks old and were at anthesis. Based on the methods of Thirkell, Pastok, et al (2019), three cores constructed from PVC tubing (length 80 mm, diameter 18 mm), with windows (50 mm × 12 mm) cut in the lower two-thirds of each side were inserted into each of the plant pots ( Figure 1). These windows and the bottom of each core were covered in a 20 µm nylon mesh which prevented penetration by plant roots but allowed AMF hyphal ingrowth.…”
Section: P 15 N and 14 C Isotope Tracingmentioning
confidence: 99%
“…In both cultivars, allowing AMF access to the labeled core resulted in greater 15 N label assimilation in barley shoots, suggesting AMF contributed to N uptake. Mycorrhizal acquisition of N has been demonstrated in barley (Wilkinson et al, 2019), and wheat (Miransari et al, 2009;Thirkell, Pastok, et al, 2019;Zhu et al, 2016),…”
Section: Amf May Mediate Barley P Assimilation Response To Ecomentioning
confidence: 99%
“…There are many examples where DH mapping populations have been used successfully for the construction of genetic maps of hexaploid wheat and QTL mapping ( Blake et al, 2019 ). One example of the prominent use of DH lines in the identification of marker-trait associations in the UK is by having a national reference population, in this case, Avalon × Cadenza (A × C) ( Griffiths et al, 2009 ; Griffiths et al, 2012 ; Allen et al, 2011 ; Bai, Liang & Hawkesford, 2013 ; Ma et al, 2015 ; Farré et al, 2016 ; Coulton et al, 2020 ; Thirkell, Pastok & Field, 2020 ), which was developed as part of the UK Wheat Genetic Improvement Network ( WGIN, 2008 ) and tested for agronomic traits in different regions the world ( Ma et al, 2015 ; Farré et al, 2016 ),…”
Section: Introductionmentioning
confidence: 99%